Influence of glottal closure on the phonatory process in ex vivo porcine larynges - Birk, Veronika (J Acoust Soc Am, 2017)
Many cases of disturbed voice signals can be attributed to incomplete glottal closure, vocal fold oscillation asymmetries, and aperiodicity. Often these phenomena occur simultaneously and interact with each other, making a systematic, isolated investigation challenging. Therefore, ex vivo porcine experiments were performed which enable direct control of glottal configurations. Different pre-phonatory glottal gap sizes, adduction levels, and flow rates were adjusted. The resulting glottal closure types were identified in a post-processing step. Finally, the acoustic quality, aerodynamic parameters, and the characteristics of vocal fold oscillation were analyzed in reference to the glottal closure types. Results show that complete glottal closure stabilizes the phonation process indicated through a reduced left-right phase asymmetry, increased amplitude and time periodicity, and an increase in the acoustic quality. Although asymmetry and periodicity parameter variation covers only a small range of absolute values, these small variations have a remarkable influence on the acoustic quality. Due to the fact that these parameters cannot be influenced directly, the authors suggest that the (surgical) reduction of the glottal gap seems to be a promising method to stabilize the phonatory process, which has to be confirmed in future studies.